2016
DOI: 10.2527/jas.2015-0268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sustained reduction of enteric methane emissions with dietary supplementation of 3-nitrooxypropanol on growth performance of growing and finishing beef cattle1

Abstract: The study objective was to evaluate the effects of sustained reduction of enteric methane (CH) emissions with dietary supplementation of the inhibitor 3-nitrooxypropanol (NOP) on growth rate and feed conversion efficiency of growing and finishing beef cattle. Eighty-four crossbred steers were used in a 238-d feeding study and fed a backgrounding diet for the first 105 d (backgrounding phase) and transition diets for 28 d followed by a finishing diet for 105 d (finishing phase) with 3 doses of NOP (0, 100, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
76
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 25 publications
13
76
1
4
Order By: Relevance
“…New feed was delivered to the pen bunks beginning at 0600 h, and although the cattle had unrestricted access to feed, it appeared the cattle consumed much of the feed in the morning. The greater impact of 3-NOP later in the day follows the results from other studies, which show a peak in CH 4 emission a few hours after feeding (Vyas et al, 2016).…”
Section: Methane Reductions Using Concentration Ratiosupporting
confidence: 88%
See 1 more Smart Citation
“…New feed was delivered to the pen bunks beginning at 0600 h, and although the cattle had unrestricted access to feed, it appeared the cattle consumed much of the feed in the morning. The greater impact of 3-NOP later in the day follows the results from other studies, which show a peak in CH 4 emission a few hours after feeding (Vyas et al, 2016).…”
Section: Methane Reductions Using Concentration Ratiosupporting
confidence: 88%
“…Those studies measured CH 4 emissions using whole‐animal chambers. However, also using chambers, Vyas et al (2016) reported 84% reduction in CH 4 from cattle fed a barley‐based diet with 3‐NOP (200 mg kg −1 DM daily). The magnitude of CH 4 reduction observed in our study is realistic.…”
Section: Resultsmentioning
confidence: 99%
“…2019R1F1A1056904). ments methods of CH 4 emissions among all used studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25] (Table 1). In short, the administration methods of NOP were direct administration via cannula, top dressed, and mixed with diet.…”
Section: Funding Sourcesmentioning
confidence: 99%
“…The NOP is a structural analogue of methyl coenzyme-M, which inhibits the activity of methyl coenzyme-M reductase related to the final step of methanogenesis [11]. Until now, total 14 in vivo studies using NOP supplementation were performed on various domestic ruminants, including sheep [12], beef cattle [13][14][15][16][17][18][19], and dairy cattle [20][21][22][23][24][25]. According to the results of previous studies using NOP in vivo, the CH 4 emissions and proportion of acetate (% total volatile fatty acids, VFA) clearly decreased, whilst the proportion of propionate (% total VFA) significantly increased, but any adverse effects were not detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation